Microcomputed tomography a noninvasive method to evaluate the fit of a restoration as compared to conventional replica technique - Sabita M Ram; Nishita Narendra Ranadive; Jyoti B Nadgere (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study was to compare the assessment methods used to evaluate the fit of Ni-Cr metal copings. Settings and Design: Comparative- Invitro study design. Materials and Methods: A stainless steel die simulating a prepared first maxillary premolar was used as a master die. Wax pattern copings were fabricated by the conventional dipping wax technique (n = 20) on the master die and were cast in Ni-Cr alloy. The finished copings were fitted on the master die and scanned by the micro-computed tomography (CT) scanner. Multiple projections of the sample were reconstructed to evaluate the marginal and internal fit at 5 predetermined locations. The same copings were used for the replica technique and were evaluated under a stereomicroscope in the same locations. Statistical Analysis Used: Shapiro-Wilk's test and Unpaired t-test Results: The marginal fit values observed were 127.71 and 95.06 μm, chamfer area fit values were 151.97 and 132.7 μm, axial area fit values were 62.36 and 46.14 μm, axio-occlusal area fit values were 139.52 and 123.6 μm, occlusal area fit values were slightly higher with 217.91 and 193.1 μm, respectively, in replica and micro-CT technique. There was no statistically significant difference observed in the fit between the two assessment methods (α > 0.05). Conclusions: There was no difference observed in the marginal and internal fit of Ni-Cr metal copings with the two methods of assessment. However, the micro-CT technique proved to be simpler, noninvasive, and time-saving assessment method.